2014
DOI: 10.1007/s12262-014-1170-y
|View full text |Cite
|
Sign up to set email alerts
|

Robot-Assisted Radical Prostatectomy vs. Open Retropubic Radical Prostatectomy for Prostate Cancer: A Systematic Review and Meta-analysis

Abstract: Open retropubic radical prostatectomy (ORP) remains the "gold standard" for surgical treatment of clinically localized prostate cancer (PCa). Robot-assisted radical prostatectomy (RARP) is a robotic surgery used worldwide. The aim of this study is to collect the data available in the literature on RARP and ORP, and further evaluate the overall safety and efficacy of RARP vs. ORP for the treatment of clinically localized PCa. A literature search was performed using electronic databases between January 2009 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
(36 reference statements)
0
11
0
Order By: Relevance
“…Robot‐assisted radical prostatectomy (RARP) is an appropriate surgical technique for the treatment of clinically localized prostate cancer because it offers faster recovery of erectile function than other surgical modalities, such as open and laparoscopic radical prostatectomy . Several recent reports have demonstrated that nerve‐sparing (NS) radical prostatectomy contributes not only to the recovery of erectile function, but also to the improvement of urinary incontinence .…”
Section: Introductionmentioning
confidence: 99%
“…Robot‐assisted radical prostatectomy (RARP) is an appropriate surgical technique for the treatment of clinically localized prostate cancer because it offers faster recovery of erectile function than other surgical modalities, such as open and laparoscopic radical prostatectomy . Several recent reports have demonstrated that nerve‐sparing (NS) radical prostatectomy contributes not only to the recovery of erectile function, but also to the improvement of urinary incontinence .…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1 shows the process of inclusion and exclusion of studies during the systematic literature search. Details on search terms, outcomes of interest, methods for accounting for bias, and so forth are outlined in the figure legend [5,[15][16][17][18][19][20][21][22][23].…”
Section: Methodsmentioning
confidence: 99%
“…Outcomes of interest included age, transfusions, LOS, individual perioperative complication rates, operative time, PACU time, hernia rates out to 3 years (incisional and inguinal), and continence/incontinence and potency/impotency out to 3 years. Nine systematic reviews were identified [5,[16][17][18][19][20][21][22][23]. The lack of RALP vs. RRP RCTs has resulted in criticisms of comparisons between RALP and RRP due to differences in patient characteristics; patients undergoing RALP tend to be younger and in the earlier stages of the disease, predisposing them to better outcomes.…”
Section: Hospital Economic Modelmentioning
confidence: 99%
“…We also found several meta-analyses. [8][9][10][11][12][13][14][15][16][17][18] None of these found any difference in mortality or other cancer-related outcomes between RALP and RRP. With regards to the complications of urinary incontinence and sexual dysfunction, results were mixed, with some analyses finding a modest benefit to robotic surgery, and some analyses finding no difference.…”
Section: Related Literaturementioning
confidence: 99%